A silver alginate coated dressing to reduce catheter-related bloodstream infection (CRBSI) among adult ICU patient: a randomised controlled trial - Ruslan, Muhammad Rosnal (2020)
Background: Catheter-related bloodstream infection (CRBSI) is a bloodstream infection related to the presence of a central venous catheter (CVC) in the patient's vein. Many types of dressing have been used on CVC to reduce the numbers of CRBSI. However, the most ideal dressing to reduce CRBSI is still under study. The aim of this study is to evaluate the effectiveness of silver alginate dressing in reducing CRBSI in comparison to conventional dressing. Methods: A total of 98 ICU patient from Hospital Universiti Sains Malaysia, Kelantan that were indicated for CVC insertion were divided randomly into two groups; Group 1 for silver alginate dressing (n=49) and Group 2 for conventional dressing (n=49). The CVC was subsequently applied with either silver alginate dressing or conventional dressing. Blood culture was withdrawn from the CVC lumen on day 6 of catheter placement or earlier if infection was suspected or prior removal of the catheter in the patient whose catheter no longer needed before 6th day. CVC was removed as soon as possible if no longer required or suspicious of catheter-related infection or when the duration was more than 14 days. Demographic data, catheter colonization, the occurrence of local infection and CRBSI will be recorded. Results: No subject in silver alginate group developed CRBSI and one subject in the conventional dressing group developed CRBSI, respectively (n=0, 0% vs n=1, 2.1%, P=0.99). Total of four subjects developed catheter colonization: one subject in silver alginate group and three subjects in the conventional dressing group, respectively (n=1, 2.1% vs n=3, 6.1%, P=0.617). Total of four subjects developed local infection: one subject in silver alginate group and three subjects in the conventional dressing group, respectively (n=1, 2.1% vs n=3, 6.1%, p=0.617). Silver alginate dressing group showed less proportion of CRBSI, catheter colonization and local infection compared to conventional dressing. However, these results were not statistically significant with p>0.05. Conclusion: Silver alginate dressing is not effective in reducing CRBSI, catheter colonization and local infection compared to conventional dressing.